p-doped 1.3 μm InAs/GaAs quantum-dot laser with a low threshold current density and high differential efficiency - Liu, H. Y.; Liew, S. L.; Badcock, T.; Mowbray, D. J.; Skolnick, M. S.; Ray, S. K.; Choi, T. L.; Groom, K. M.; Stevens, B.; Hasbullah, Nurul Fadzlin; Jin, C. Y.; Hopkinson, M.; et al. (American Institute of Physics, 2006)
Amodification of the thickness of the low-growth- emperature component of the GaAs spacer layers in multilayer 1.3 um InAs/GaAs quantum-dot (QD) lasers has been used to significantly improve device performance. For a p-doped seven-layer device, a reduction in the thickness of this component from 15 to 2 nm results in a reduced reverse bias leakage current and an increase in the intensity of the spontaneous emission. In addition, a significant reduction of the threshold current density and an increase of the external differential efficiency at room temperature are obtained. These improvements indicate a reduced defect density, most probably a combination of the selective elimination of a very low density of dislocated dots and a smaller number of defects in the thinner low-growth-temperature component of the GaAs spacer layer.